Pemberdayaan Masyarakat Dalam Peningkatan Ekonomi Di Desa Cikalong Kecamatan Cilamaya Wetan - Muhammad Rizky Mubaroq; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
In promoting public empowerment that a great role must be played by the cadet reef. Human resources are indispensable in creating a creativity and innovation in employed performance so that it can give birth to a targeted work program and the concept of empowerment to society. The assessment of the performance of the cadet reef is seen as coordinating for village government. That the highly ordered assessment of the village affects the effectiveness of the performance produced by the cadet reef. The lack of human resource interest in the teachers' village has resulted ina weakening of the work programs undertaken, which is because many societies are more self-centered and therefore are difficult to contribute or join the cadets. The research method used is a descriptive study method with a qualitative approach by observing, interviewing and documenting previously determined resources. The results show that the effectiveness of the performance of the caduna reef is still less than optimal because of the lack of human resources and lack of coordination with village authorities, but in achieving a work program can increase people's satisfaction.